THE INFLUENCE OF INITIAL CAPITAL AND PROVIDING CREDIT ON THE INCOME LEVEL OF SMALL AND MEDIUM ENTERPRISES IN THE VILLAGE SIMPANG MAMPLAM BIREUEN DISTRICT - Silfiani; Anisah Turrahmi; Zaituni; Dina Hendiyani (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Empowering small and medium businesses is a strategic step to improve and strengthen the economy of some communities in Indonesia. This research aims to determine how initial capital and credit provision affect the income level of small and medium businesses. This research was conducted in Simpang Mamplam village in October – February of the 2023/2024 academic year. The samples taken in the research were 47 MSMEs. This research uses a quantitative research approach. The research instrument is a questionnaire. The research results show that initial capital and the provision of credit both influence the establishment of SMEs so that they can increase the income of small and medium businesses in Simpang Mamplam village, Simpang Mamplam District, Bireuen Regency.